An Ecological and Societal Approach to Biological Control - Eilenberg, J.; Eilenberg, J.; Hokkanen, Heikki M. T.; Hokkanen, Heikki M. T. (Progress in Biological Control,, 2006)
Biological control is among the most promising methods for control of pests (including vectors), diseases and weeds. In this book ecological and societal aspects are for the first time treated together. In an ecological approach the aim is to evaluate the significance of certain biological properties like biodiversity and natural habitats. Also, it is important to see biological control from an organic (or ecological) farming point of view. In a societal approach terms like ‘consumer’s attitude’, ‘risk perception’, ‘learning and education’ and ‘value triangle’ are recognised as significant for biological production and human welfare.